AMALAN PENAMBAHBAIKAN KUALITI BERTERUSAN DALAM INSTITUSI PENDIDIKAN - Mua’azam Mohamad; Yahya Don; Muhamad Dzahir Kasa (Proceedings of The ICECRS, 2016)
With the increasing demand in improving quality education system, the Malaysian Education Ministry has recently adopted a policy aimed at practicing continuous quality improvement (CQI) at all levels and across all states. The key goal is to achieve changes in practice which improve education outcomes. This paper includes the systematic literature review to describe the scenario of quality management practices in industry and quality improvement approaches at various levels in education systems. Several identified themes were discovered ie the importance of continuous improvement programs, quality management systems and readiness to implement the quality improvement practices. Future research should include the psychology aspects in testing the effectiveness of quality improvement practices.